Protocol for the residents in action pilot cluster randomised controlled trial (RiAT): evaluating a behaviour change intervention to promote walking, reduce sitting and improve mental health in physically inactive older adults in retirement villages. Issue 6 (23rd June 2017) - Thøgersen-Ntoumani, Cecilie; Wright, Ashlene; Quested, Eleanor; Burton, Elissa; Hill, Keith D; Cerin, Ester; Biddle, Stuart J H; Ntoumanis, Nikos
Abstract : Introduction: Ageing is accompanied by increased risks of chronic disease, declined functioning and increased dependency. Physical activity is critical to retaining health and independence, but the majority of older people are insufficiently physically active to achieve these benefits and have high levels of sedentary (sitting) time. Activity programmes are often offered in retirement villages; however, their uptake is limited. Furthermore, although the physical environment in and around these villages can play an important role in decisions to be physically active, its role is often overlooked by research in these settings. We aim to develop, implement and evaluate a proof-of-concept motivationally embellished intervention designed to increase walking, reduce sitting and improve mental health in residents in retirement villages. Methods and analysis: This will be a 16-week pilot intervention using a cluster randomised design with retirement villages as the unit of randomisation and residents as the unit of assessment. Fourteen retirement villages around Perth, Western Australia, will be recruited for the intervention. Objective audits of neighbourhood environments around each village will be completed using the Pathway Environmental Audit Tool. Seven villages will be randomised to the experimental arm and seven to the control arm. Only participants in the experimental arm will receive motivational training. All outcomes will be assessed at baseline, end of intervention and 6-month follow-up. Changes in physical activity levels, sitting time and mental health will be examined. Multilevel modelling will be used to analyse the data. A mixed methods process evaluation will also be conducted. Ethics and dissemination: Ethics approval was granted by Curtin University's Human Research Ethics Committee (HREC2016-0187). The results of the study will be disseminated via peer-reviewed publications, conference presentations and reports to, and seminars with, stakeholders. Trial registration: The trial is registered with the Australian New Zealand Clinical Trials Registry: ACTRN12616001177448.